2020
DOI: 10.3390/w12051512
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Water Buffer Capacity of Two Morphometrically Different, Degraded, Urban Lakes

Abstract: The research was conducted in Karczemne Lake (area, 40.4 ha; maximum (max.) depth, 3.2 m) and Klasztorne Małe Lake (area, 13.7 ha; max. depth, 20.0 m) located in the Kashubian Lake District (Northern Poland). From the beginning of the 1950s, these reservoirs have received municipal and storm wastewater. The long-term process of lake contamination has shaped the specific buffer capacity conditions and influenced the circulation of carbonate and bicarbonate in the water of these ecosystems. Extremely high concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…The more intensive the primary production, the clearer the difference in the alkalinity and Ca content between the surface and the bottom. A similar situation was recorded by Grochowska [80] for the degraded Lake Klasztorne Małe.…”
Section: Calcium (Ca 2+ )supporting
confidence: 85%
“…The more intensive the primary production, the clearer the difference in the alkalinity and Ca content between the surface and the bottom. A similar situation was recorded by Grochowska [80] for the degraded Lake Klasztorne Małe.…”
Section: Calcium (Ca 2+ )supporting
confidence: 85%
“…Water temperature and dissolved oxygen are variables inversely related (Lewis 1987; Khani and Rajaee 2017; Koralay et al 2018); nevertheless, in this study, a direct relationship was observed, these variations might be explained more by biological effects (photosynthesis-respiration) than by physical aspects (Cervantes-Martínez and Gutiérrez-Aguirre 2015). pH values were closer to the neutrality, probably due to the limestone buffer, according to Razo et al (2004) and Grochowska (2020). The electrical conductivity recorded in this work (3247-3407 µS/cm 3 ) is characteristic of freshwater systems in central-north Mexico due to the dominant processes of evaporation and salt precipitation (Alcocer and Escobar 1996).…”
Section: Resultsmentioning
confidence: 50%
“…The presence of calcium carbonate and magnesium carbonate contributes carbonate ions to the buffering system. Alkalinity is commonly related to hardness, as the main alkalinity source often comes from carbonate rocks (limestone), made up mostly of CaCO3 [58,59]. It is known that the process of buffering calcite is dominant in the pH range of 6.5-7.5 [60].…”
Section: Discussionmentioning
confidence: 99%